Soil Temperature Regimes under Mixed Dipterocarp Forests of Peninsular Malaysia - Nik, Abdul Rahim; Kasran, Baharuddin; Hassan, Azman (1986)
Soil temperature regimes of forested and open conditions at selected depths of 5, 10, 20 and 30 cm, were reported based on data collected over a two-year period. Results showed that temperature of soil under forest cover was consistently lower than of the open by 4 to GOC due to 'shading effect' of forest cover. The top 5 cm layer in the open showed the greatest variation whilst insignificant differences were observed among layers under forest. Weighted average soil profile temperature for both conditions seemed to follow closely the mean air temperature. However, open air temperatures consistently recorded lower values.